2019
DOI: 10.1177/1350650119866028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of couple stress parameter on steady-state and dynamic characteristics of three-lobe journal bearing operating on TiO2 nanolubricant

Abstract: Steady-state and dynamic performance parameters of three-lobe fluid film bearing, operating on TiO2 nanolubricant have been obtained. The effective viscosity for a given volume fraction of TiO2 nanoparticle in base fluid is obtained by using Krieger–Dougherty viscosity model. Various bearing performance parameters are obtained by solving remodeled Reynolds equation, which includes couple stress parameter. The stiffness and damping coefficients are also obtained for different values of the couple stress paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…They studied the effects of couple stress parameter on the static and dynamic characteristics of three-lobe journal bearings. 36 In this paper by considering Tio2 nanoparticles in Newtonian lubricant as an additive according to Refs. 37,38 the results show that increasing the couple stress parameter shows a very significant improvement in dynamic coefficients and increasing the load carrying capacity, while decreasing the attitude angle and the friction variable.…”
Section: Introductionmentioning
confidence: 99%
“…They studied the effects of couple stress parameter on the static and dynamic characteristics of three-lobe journal bearings. 36 In this paper by considering Tio2 nanoparticles in Newtonian lubricant as an additive according to Refs. 37,38 the results show that increasing the couple stress parameter shows a very significant improvement in dynamic coefficients and increasing the load carrying capacity, while decreasing the attitude angle and the friction variable.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that adding a small amount of long-chain polymer to the lubricant can effectively improve the load capacity performance of the friction pair. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] A small amount of long-chain polymer changes the fluid characteristics of the lubricant, changing the lubricant fluid characteristics from Newtonian fluid to couple stress fluid. From the perspective of engineering applications, such measures are simple and effective.…”
Section: Introductionmentioning
confidence: 99%
“…The current couple stress fluid lubrication theory is relatively mature, and the mathematical model of couple stress fluid lubrication is derived based on Stokes' microcontinuum theory. Many scholars have applied the mathematical model of coupled stress fluid lubrication to study the static and dynamic performance of various types of friction pairs such as journal bearing, [1][2][3][4][5][6][7] porous journal bearing, 8 double-layered journal bearing, 9 two-lobe journal bearing, [10][11][12] three-lobe journal bearing, 13 gas foil bearing, 14 and sliding bearing. 15 Compared with Newtonian fluid, coupled stress fluid can effectively improve the load capacity of the friction pair.…”
Section: Introductionmentioning
confidence: 99%
“…It increases the film thickness, which results in less wear of direct metal-to-metal contact and improves bearing life (Chippa and Sarangi, 2013). Numerous researchers examined couple stresses influence on bearings systems characteristics, such as journal bearings (Lin, 1997; Kumar and Kakoty, 2020) and porous journal bearings (Bhattacharjee et al , 2019a; Bhattacharjee et al , 2019b; Patil et al , 2020). Wang et al (2002) investigated numerically a journal bearing performance under dynamical loading using couple stress fluids.…”
Section: Introductionmentioning
confidence: 99%